Modern management of arrhythmias. Issue 964 (3rd February 2006) - Hall, M C S; Todd, D M
Abstract : The specialist management of arrhythmias has changed significantly over the past decade. This article outlines current management strategies for atrial flutter and atrial fibrillation, with particular emphasis on curative strategies with catheter ablation and the recent data on rhythm compared with rate control strategies. The expanding role of catheter ablation in the treatment of a wide variety of supraventricular and ventricular arrhythmias is discussed. The current evidence for implantable cardioverter defibrillators in the prevention of sudden cardiac death is summarised. The article also highlights the increasing recognition of a number of inherited syndromes that predispose to sudden cardiac death (for example, Brugada and long QT syndromes).